A novel kind of electrohydraulic loading system based on friction for actuator test. (15th May 2019) - Jing, Chenghu; Xu, Hongguang
Conventional electric or electrohydraulic load simulator is disturbed by the motion of the tested system. To eliminate the strong motion disturbance and improve loading performance, a novel kind of friction electrohydraulic loading system is proposed. The mechanism of friction electrohydraulic loading system is described in detail. The math model for the loading torque and the input signal has been deduced, which indicates that this proposed friction electrohydraulic loading system has no disturbances resulting from tested actuators under ideal conditions. However, friction coefficient is time-varying and uncertain. The friction device increases the load inertia of the actuator. The additional inertia may affect the loading performance. The structure mechanism has been optimised to reduce the rotary inertia. To verify the loading performance of friction electrohydraulic loading system, simulations and experiments are carried out. Compared with conventional electrohydraulic load simulator, the theoretical analysis and experimental results validate the feasibility of the friction electrohydraulic loading method. The novel friction electrohydraulic load simulator, with a simple control principle and easy engineering constructability, can provide accurate torque simulation for actuator test.